Fahien reconsidered: Pleistocene exploitation of wild bananas and Holocene introduction of Musa cultivars to Sri Lanka. (23rd July 2019) - De Langhe, Edmond; Vrydaghs, Luc; Perrier, Xavier; Denham, Tim
ABSTRACT: A recent publication on the phytolith assemblage at Fahien rockshelter, Sri Lanka (Premathilake and Hunt) is argued to represent: the exploitation of wild Musa acuminata and M. balbisiana during the Late Pleistocene; the introduction of edible diploid cultivars from the Southeast Asia–New Guinea region during the early to mid‐Holocene; the generation and cultivation of triploid banana hybrids on Sri Lanka before 6194–5994 cal bp ; and the subsequent spread of derived triploid cultivars to mainland India and westward to Africa. A careful review of the archaeobotanical research presented by Premathilake and Hunt, in the context of broader multidisciplinary evidence (agronomy, archaeobotany, genetics and linguistics) for the domestication and spread of banana cultivars, indicates that three main aspects of their argument are problematic: the lack of clarity in the characterization of banana domestication in the past; the methods used to discriminate phytoliths into banana taxa; and the promotion of Sri Lanka as a source region rather than a recipient of banana cultivars. Following reconsideration, the Fahien evidence is consistent with previous interpretations for the origins of diploid and significant triploid cultivars outside of Sri Lanka and dispersal to that island. © 2019 John Wiley & Sons, Ltd.